2018
DOI: 10.1002/acm2.12460
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of combined use of ArcCheck® detector and portal dosimetry for delivery quality assurance of head and neck and prostate volumetric‐modulated arc therapy

Abstract: PurposeTo assess the efficiency of combined use of ArcCheck® detector (AC) and portal dosimetry (PDIP) for delivery quality assurance of head and neck and prostate volumetric‐modulated arc therapy.Materials and methodsMeasurement processes were studied with the Gamma index method according to three analysis protocols. The detection sensitivity to technical errors of each individual or combined measurement processes was studied by inserting collimator, dose and MLC opening error into five head and neck and five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…The results obtained when trying to detect MLC errors of our AC protocols are comparable with the results of their study.Delta 4 shows the same behavior as the ArcCHECK Phantom for both global gamma protocols with 3%/3 mm and 2%/2 mm.Moliner et al investigated, among other QA tools, the AC detector. The results of this study, using collimator, dose and MLC errors, are in agreement with our investigation of gamma criteria 3%/3 mm and 2%/2 mm for all treatment sites 10. Log files are generated by the linac and therefore are insensitive to miscalibration of any component such as leaf position.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…The results obtained when trying to detect MLC errors of our AC protocols are comparable with the results of their study.Delta 4 shows the same behavior as the ArcCHECK Phantom for both global gamma protocols with 3%/3 mm and 2%/2 mm.Moliner et al investigated, among other QA tools, the AC detector. The results of this study, using collimator, dose and MLC errors, are in agreement with our investigation of gamma criteria 3%/3 mm and 2%/2 mm for all treatment sites 10. Log files are generated by the linac and therefore are insensitive to miscalibration of any component such as leaf position.…”
supporting
confidence: 89%
“…The agreement for both the reference and the non-error-free plans for AC gamma passing rate is consistent with previous research not using log files. 3,[9][10][11]13,14 Many studies evaluated the The essential strength of our investigation is that all measurements were performed with AC, LW and ionization chamber at the same time. Log files were generated during AC measurements of all plans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the medical physics field, there appears to be some confusion between the Winston-Lutz test and the End-to-End test in the single iso-multiple mets treatment QA process. [13] demonstrated that even the linac collimator has 2˚ -3˚ mechanical error and MLC has 0.5 mm mechanical error, the patient specific QA still cannot 100% to detect the those errors.…”
Section: Discussionmentioning
confidence: 99%